2021
DOI: 10.1007/s43393-021-00061-9
|View full text |Cite
|
Sign up to set email alerts
|

Food-grade expression of multicopper oxidase with improved capability in degrading biogenic amines

Abstract: Biogenic amines (BAs) are potential amine hazards that are detected in fermented foods and alcoholic beverages. Excessive intake of BAs may lead to allergic symptoms such as difficulty in breathing, nausea, and vomiting. Degradation of BAs by multicopper oxidase (MCO) is a promising method as it has little effect on the fermentation process, food nutrition, and flavor. However, the application of MCO in food industry was restricted due to its poor catalytic properties and low productivity. In this work, food-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…More importantly, the TY-11 genome carried a multicopper oxidase domain-containing protein (LPJCKDFM_00777). Multicopper oxidase (MCO)-mediated BAS degradation is an auspicious method as the fermentation process, food nutrition, and flavor are unaffected ( 42 ). This genome also contained nitroreductase (LPJCKDFM_00111), a flavoenzyme that catalyzes the reduction of the nitro groups on nitroaromatic and nitroheterocyclic compounds in a NAD ( P )H-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the TY-11 genome carried a multicopper oxidase domain-containing protein (LPJCKDFM_00777). Multicopper oxidase (MCO)-mediated BAS degradation is an auspicious method as the fermentation process, food nutrition, and flavor are unaffected ( 42 ). This genome also contained nitroreductase (LPJCKDFM_00111), a flavoenzyme that catalyzes the reduction of the nitro groups on nitroaromatic and nitroheterocyclic compounds in a NAD ( P )H-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Another aspect, the TY-11 genome carried multicopper oxidase domain-containing protein (LPJCKDFM_00777). Multicopper oxidase (MCO) mediated BAS degradation is an auspicious method as the fermentation process, food nutrition, and flavour are unaffected [44]. This genome also contains nitroreductase (LPJCKDFM_00111), a flavoenzyme that catalyzes the reduction of the nitro groups on nitroaromatic and nitroheterocyclic compounds in a NAD (P)H-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…These involve important enzymes, such as D-lactic acid Another aspect, the TY-11 genome carried multicopper oxidase domain-containing protein (LPJCKDFM_00777). Multicopper oxidase (MCO) mediated BAS degradation is an auspicious method as the fermentation process, food nutrition, and flavour are unaffected [44].…”
Section: The Most Prevalent Harmful By-products Of Labsmentioning
confidence: 99%
“…Additionally, Xu and Fang (2019) reported that L. fermentum recombinant laccase can degrade histamine and tyramine by 51.6% and 40.9%, respectively, as well as other BAs such as tryptamine, PEA, putrescine, cadaverine, and spermidine [16]. Ni et al (2022) demonstrated that a salt-tolerant, mutant recombinant laccase from B. amyloliquefaciens effectively degraded histamine, tyramine, and putrescine by 25%, 20%, and 7%, respectively, in a 50 mM sodium phosphate buffer (pH 4.5) [54]. Recently, Wang and colleagues (2022) reported the ability of L. sakei recombinant laccase to degrade histamine and tyramine in the absence of mediators at various ethanol concentrations, with degradation rates of approximately 20% and 25%, respectively, when exposed to 20% ethanol, and in food matrices such as surimi and grape juice [20].…”
Section: Discussionmentioning
confidence: 99%